Glial heterotopia of maxilla: A clinical surprise - Santosh Kumar Mahalik; Toijam S Lyngdoh; Prema Menon; Kushaljit Singh Sodhi; Rakesh Kumar Vashishta; Ravi P Kanojia; KLN Rao (Wolters Kluwer Medknow Publications, 2011)
Glial heterotopia is a rare congenital mass lesion which often presents as a clinical surprise. We report a case of extranasal glial heterotopia in a neonate with unusual features. The presentation, management strategy, etiopathogenesis and histopathology of the mass lesion has been reviewed.